Internal conflict faced by the main character in greenland movie - Yasa, I Gusti Ngurah; Candra, Komang Dian Puspita; Winarta, Ida Bagus Gede Nova (Institut Pariwisata dan Bisnis Internasional, 2022)
This study analyzed the internal conflict faced by the main character and also the source of conflict in Greenland Movie. The data of this study were taken from the Greenland movie. The data were analyzed qualitatively by using theory from Reaske (1966) and theory from Bartos and Wehr (2002). The collected data in this study were taken by observation and note taking technique. The finding of this result show that main character here has a lot of internal conflict and the source of conflict as the result of Goal Incompatibility and Hostility such as different opinion, anger, disappointed, sadness and emotional that faced by the main character, because the main character in the movie must struggle for his family to be save and also struggle with his heart and mentally.